2013
DOI: 10.1186/1476-069x-12-83
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand tobacco smoke exposure and heart rate variability and inflammation among non-smoking construction workers: a repeated measures study

Abstract: BackgroundAlthough it has been well recognized that exposure to secondhand tobacco smoke (SHS) is associated with cardiovascular mortality, the mechanisms and time course by which SHS exposure may lead to cardiovascular effects are still being explored.MethodsNon-smoking workers were recruited from a local union and monitored inside a union hall while exposed to SHS over approximately 6 hours. Participants were fitted with a continuous electrocardiographic monitor upon enrollment which was removed at the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…We did not find significant differences between baseline and post-shift levels in the levels of any of CRP, IL-6, IL-8, and IL-10. This finding is in contrast to what was previously independently documented by Zhang and Bruno in this study population 26, 27 . Whereas Zhang et al and Bruno et al had used paired samples from these participants on a non-weld day at baseline and next morning as post-exposure samples in assessing the effect of secondhand smoke exposure, we restricted our samples to the weld day because we were interested in determining the effect of weld fume exposure.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find significant differences between baseline and post-shift levels in the levels of any of CRP, IL-6, IL-8, and IL-10. This finding is in contrast to what was previously independently documented by Zhang and Bruno in this study population 26, 27 . Whereas Zhang et al and Bruno et al had used paired samples from these participants on a non-weld day at baseline and next morning as post-exposure samples in assessing the effect of secondhand smoke exposure, we restricted our samples to the weld day because we were interested in determining the effect of weld fume exposure.…”
Section: Discussioncontrasting
confidence: 99%
“…We may therefore be missing the right time window to capture observable differences between baseline and post-exposure mediator levels. Next-morning samples have been shown to capture better changes in inflammatory markers following injurious stimuli 26, 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are also supported by other studies that looked at acute effects of SHS on HRV and found consistent decreases in SDNN as soon as subjects were exposed (Pope et al 2001) or right after exposure (Zhang et al 2013; Wilson et al 2010). The effect of active smoking on heart rate variability has been studied extensively.…”
Section: Discussionsupporting
confidence: 91%
“…Acute effects of exposure to SHS on HRV, a marker of autonomic tone, have been shown in previous studies using cross-sectional approaches (Pope 2001; Wilson et al 2010; Zhang et al 2013), but Rajkumar et al present results of the first prospective study to examine effects of reducing SHS exposure on HRV, with addition of a dose-response in a real-world setting. Alterations in HRV have been linked to changes in particulate matter air pollution in a number of studies, but the results have not always been consistent, perhaps due to differences in methods and host factors (age, sex, comorbidities, etc) between studies (Pieters et al 2012).…”
mentioning
confidence: 97%